Is it time for India to set social media age limits for adolescents? - Om Prakash (Indian Journal of Psychiatry)
The rapid integration of social media into the lives of Indian adolescents presents a complex mix of benefits and challenges, particularly in the realms of mental health, online safety, and digital literacy. While age restrictions or outright bans may offer protections against risks like cyberbullying, exposure to harmful content, and increased screen time, they also carry potential drawbacks, including digital exclusion, disruption of peer support networks, and limited access to educational and mental health resources. This viewpoint article examines the multifaceted challenges of implementing social media age restrictions in India, considering the diversity in digital literacy, sociocultural factors, and infrastructural disparities between urban and rural areas. Recognizing these complexities, the article proposes alternative approaches, including comprehensive digital literacy programs, enhanced parental involvement, age-appropriate content moderation, and flexible, phased access to social media. By advocating for a balanced, collaborative approach involving policymakers, educators, parents, and platform providers, this article emphasizes the importance of creating a safe yet empowering digital environment that nurtures responsible online engagement. Such a nuanced policy framework would allow Indian adolescents to safely benefit from the positive aspects of social media while minimizing risks, ultimately fostering a generation of resilient, informed digital citizens.